Organ Donation Attitudes Among Individuals With Stage 5 Chronic Kidney Disease. Issue 8 (August 2018) - Loughery, Caitlin; Andrews, Ann M.; Zhang, Nanhua; Smith, Allyce Haney; Resnicow, Ken; Chapman, Remonia; Riley, Holly Jenkins; Stav, Sheri; Yee, Jerry
Abstract : Background: The need for transplantable organs drastically outweighs the supply. Misconceptions are a barrier to increasing the rate of donor registration. Individuals with stage 5 chronic kidney disease (CKD) may incorrectly believe they are unable to be donors; however, their attitudes have not been studied. This study aims to explore beliefs of individuals with stage 5 CKD about their ability to donate and test the validity of an organ donation scale. Methods: We examined the psychometric properties of a new 25-item organ donation scale among 554 patients with stage 5 CKD at 12 dialysis units in southeast Michigan. Patients completed surveys during dialysis treatment with assistance from a program coordinator or social worker. Results: Two subscales with good psychometric properties were identified: general benefits (α = 0.86) and general barriers (α = 0.80). For both subscales, more positive attitudes were associated with higher intent to sign up on the donor registry, suggesting validity of the scale. Conclusions: Patients who were older than 60 years, white, or of higher education status reported more positive attitudes. Misconceptions about the ability of patients with stage 5 CKD to donate are common and highlight a need for education about donor eligibility. Individuals with stage 5 CKD may be able to donate organs and tissues.